Screening for Metabolites in Earthworms Exposed to Polluted Landfill Dumpsites Using LCMS in Gombe Metropolis - Aliyu, Abubakar; Ahmed Pantami, Hamza; Adamu Abubakar , Zainab (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Metabolomics is now the state of an art used to study environmental effects such as environmental stress, pollution and climate change on the health of living organisms that lives in an environment. The study aimed to screen metabolites in earthworms exposed to polluted landfills dumpsites via identification of metabolites present in the earthworm (Bio indicators) and identify to compare metabolites found in different earthworm groups using LCMS metabolomics. Metabolites were extracted from earthworms as whole organism extracts; earthworms were washed with distilled water, flash-frozen in liquid nitrogen, and homogenized by bead-beating using mortar and pestle in 1 mL of (50:50) cold methanol/water. The content were transferred into eppendorf tube (2ml) and vortexed for (1min), centrifuged at 1800 rpm for 20 min, and the supernatant were transferred to a new tube for cleanup with 500 μL of ice-cold chloroform. The aqueous layer were dried and stored at −4°C. All samples collected were subjected to gas chromatography/ mass spectrometry (LC/MS). The RAW LC-MS data were three replicate from two dumpsites; Liji landfill dumpsite labelled L1, L2, and L3, Inex cleaners limited dump sites opposite FCE (T) Gombe labelled F1, F2, and F3. The platform, MZ mine software version 2.53 was used to processed data for LC MS based metabolomics. The outcome of this research shows the potential marker compounds that brought about the separation of the groups Liji dumpsite (L) and Inex cleaners dumpsite (F) by PC1 and PC2. It was observed that most of the identified compounds belong to (F) dumpsite, with few belonging to (L) dumpsite. The VIP metabolites which were considered as most-ranked metabolites were: 4Z,7Z,9E,11E,13Z,16Z,19Z-docosaheptaenoic acid, 1-Phenyl-1,3-dodecanedione, 5-(10’-Phenyldecyl)-Resorcinol, Beta-estradiol and 1-(7Z,10Z,13Z-hexadecatrienoyl)-3-O-beta-D-galactosyl-sn-glycerol.